2021
DOI: 10.3892/etm.2021.10244
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep behaviour disorder in Parkinson's disease (Review)

Abstract: Rapid eye movement (REM) sleep behavior disorder (RBD) is a parasomnia defined by simple or complex abnormal movements occurring in REM state, instead of the physiological muscular atonia. RBD may be idiopathic, or secondary as in the case of Parkinson's disease (PD). Several studies have confirmed that idiopathic RBD may precede with several years the onset of the specific motor characteristics of PD. The high prevalence of RBD in PD (19-70%) may be explained by several common pathophysiological pathways, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Patients may eventually develop neurodegenerative diseases after a few years or decades, and the risk of occurrence ranges from more than 30% at 5 years to more than 90% at14 years. Idiopathic RBD can be used as a pre-exercise biomarker for PD and about 20% of RBD occurred before PD and about 20% of cases had both Parkinson's disease and RBD and more than 50% of RBD occurred for several years after the clinically manifest of Parkinson's disease (Diaconu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Patients may eventually develop neurodegenerative diseases after a few years or decades, and the risk of occurrence ranges from more than 30% at 5 years to more than 90% at14 years. Idiopathic RBD can be used as a pre-exercise biomarker for PD and about 20% of RBD occurred before PD and about 20% of cases had both Parkinson's disease and RBD and more than 50% of RBD occurred for several years after the clinically manifest of Parkinson's disease (Diaconu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…REM stages are characterized by an increase in heart rate [ 1 ]. Thus, to distinguish between REM and deep-sleep, k-means clustering was conducted on all heart rate data during the deep-sleep stage ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a neurodegenerative disorder [ 1 , 2 ] of which the prevalence among people aged 60 years and older is approximately 1–3% [ 3 , 4 ]. PD risk increases with age [ 5 ], and it affects the patient’s daily activities and quality of life [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biosensor-based behavior detection approaches are also commonly applied to identify behavioral disorders in certain types of diseases, such as Parkinson’s disease (PD), Stroke, Paralysis, etc. ( Kang et al, 2010 ; Leclair-Visonneau et al, 2017 ; Alvarez et al, 2018 ; Loopez-Larraz et al, 2018 ; Migliaccio et al, 2020 ; Borzì et al, 2021 ; Diaconu et al, 2021 ). Notably, many recent studies have revealed that behavioral biomarkers might be vital indicators of Alzheimer’s disease (AD) in its initial phases ( de et al, 2014 ; Nardone et al, 2022 ; Staal et al, 2021 ), symptoms like motor behavior alteration occur before profound memory deficits ( Tippett and Sergio, 2006 ; Casper et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%